2021
DOI: 10.1152/ajpcell.00065.2021
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle progenitors are sensitive to collagen architectural features of fibril size and cross linking

Abstract: Muscle stem cells (MuSCs) are essential for the robust regenerative capacity of skeletal muscle. However, in fibrotic environments marked by abundant collagen and altered collagen organization, the regenerative capability of MuSCs is diminished. MuSCs are sensitive to their extracellular matrix environment, but their response to collagen architecture is largely unknown. The present study aimed to systematically test the effect of underlying collagen structures on MuSC functions. Collagen hydrogels were enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…These data suggest that the correct rearrangement of ECM/collagen is crucial to build an SC microenvironment appropriated for muscle growth and SC fusion. Importantly, SCs are sensitive to their extracellular matrix environment and respond differently to different collagen architecture ( Hu et al., 2021 ). Interestingly, both Tnc-C and Fn1 have been shown to remodel and adapt SC niche ( Tierney et al., 2016 ) and to regulate a feedback signal to promote symmetric division and replenish the SC pool ( Bentzinger et al., 2013 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the correct rearrangement of ECM/collagen is crucial to build an SC microenvironment appropriated for muscle growth and SC fusion. Importantly, SCs are sensitive to their extracellular matrix environment and respond differently to different collagen architecture ( Hu et al., 2021 ). Interestingly, both Tnc-C and Fn1 have been shown to remodel and adapt SC niche ( Tierney et al., 2016 ) and to regulate a feedback signal to promote symmetric division and replenish the SC pool ( Bentzinger et al., 2013 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The range of collagen concentrations investigated in this study are representative of in vivo concentrations, although the in vivo organization of collagen fibrils into cables is not reconstituted in vitro 26 , 38 , 39 . While the modulus of the collagen gels scaled with concentration, overall, the stiffnesses of the gels (0.1–0.4 kPa) were well below the physiological range 11 , 18 . YAP nuclear localization scaled with increasing collagen concentration and therefore, stiffness.…”
Section: Discussionmentioning
confidence: 93%
“…Damaged myofibers increase in stiffness causing an increase in MuSC proliferation 17 . Changes in collagen crosslinking and fibril size affect MuSCs’ capacity to differentiate into myotubes 18 . Mesenchymal stem cells (MSCs) are also known to be sensitive to their mechanical and architectural environment 19 , 20 , although FAPs specifically have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to evaluate the myotube fusion index, i.e., the fraction of nuclei incorporated in myotubes [ 42 ], for mixed gels were unsuccessful due to the low occurrence of MF20-stained cells. The influence of type I collagen on myoblasts differentiation has been reported on several occasions, pointing out that it can have either an inhibitory or a promoting effect, depending strongly on collagen organization and fiber size [ 43 , 44 , 45 ]. In particular, it was reported that myoblasts grown on fibrin-collagen hydrogels could form myotubes on flat substrates but not on threads, evidencing the key role of structure and topology of such mixed systems [ 46 ].…”
Section: Discussionmentioning
confidence: 99%